Quantitative analysis of human ras localization and function in the fission yeast Schizosaccharomyces pombe. Issue 4 (20th March 2013) - Bond, Michael; Croft, Wayne; Tyson, Richard; Bretschneider, Till; Davey, John; Ladds, Graham
Abstract Ras signalling is central to fundamental and diverse cellular processes. In higher eukaryotes ras signalling is highly complex, involving multiple isoforms, regulatory proteins and effectors. As a consequence, the study of ras activity in mammalian systems presents a number of technical challenges. The model organism Schizosaccharomyces pombe has previously proved a key system for the study of human signalling components and provides an ideal model for the study of ras, as it contains just one ras protein (Ras1p), which is non‐essential and controls a number of downstream processes. Here we present data demonstrating the quantitative analysis of three distinct Ras1‐related signalling outputs, utilizing the three most abundant human ras isoforms, H‐Ras, N‐Ras and K‐Ras4B, in Sz. pombe. Further, we have characterized the localization of these three human ras isoforms in Sz. pombe, utilizing quantitative image analysis techniques. These data indicate that all three human ras isoforms are functional in fission yeast, displaying differing localization patterns which correlate strongly with function in the regulation of pheromone response and cell shape. These data demonstrate that such yeast strains could provide powerful tools for the investigation of ras biology, and potentially in the development of cancer therapies. Copyright © 2013 John Wiley & Sons, Ltd.